Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Siswa Pada Materi Perubahan Wujud Benda di Kelas 4 SD - Adhitya Putra Pratama; Erna Zumrotun (Lembaga Bale Literasi, 2025)
This study was motivated by the low learning outcomes of fourth-grade students at SDN 02 Kedung, which were presumed to be caused by conventional teaching methods that did not actively involve students. The purpose of this study was to determine the effect of the inquiry learning model on student learning outcomes in the IPAS subject, particularly on the topic of changes in the state of matter. The research employed a quantitative approach with a one group pretest-posttest design. The test instruments were validated through a trial process to ensure their feasibility. The results showed that the average student score increased from 60.64 in the pretest to 71.35 in the posttest, with a paired sample t-test significance value of 0.001 (p < 0.05). This indicates a significant difference in learning outcomes before and after the implementation of the inquiry learning model. The model encouraged students to be more active in the learning process through activities such as observing, questioning, and drawing conclusions. These findings demonstrate that the inquiry learning model is effective in IPAS learning as it improves conceptual understanding and fosters more meaningful and contextual learning experiences.